2012
DOI: 10.1134/s1062360412030083
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of in vitro oocyte ovulation by progesterone and homologous pituitary gonadotropic hormone in sturgeons

Abstract: We showed that the percentage of sturgeon oocytes ovulating in vitro in Ringer solution modified for sturgeons (RMS) considerably depends on the concentration of sodium bicarbonate and the concentra tion of progesterone. Under optimal conditions (0.5 g/L of sodium bicarbonate and 30 ng/mL of progester one), it can be higher than 80. Oocytes that matured and ovulated under such conditions are capable of nor mal development. In the best case, approximately 70% of developing embryos (of the number of ovulated ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Although the concentration we used (1 mg ml −1 ) may seem high, our results showed that this concentration was optimal. Skoblina and Goncharov () succeeded in inducing in vitro ovulation in A. ruthenus by using 0.2 mg ml −1 of aci‐GTH, a preparation of stellate sturgeon pituitary gonadotropic hormone. In vivo ovulation is induced by MIS, which is triggered by an LH surge.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentration we used (1 mg ml −1 ) may seem high, our results showed that this concentration was optimal. Skoblina and Goncharov () succeeded in inducing in vitro ovulation in A. ruthenus by using 0.2 mg ml −1 of aci‐GTH, a preparation of stellate sturgeon pituitary gonadotropic hormone. In vivo ovulation is induced by MIS, which is triggered by an LH surge.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the result depends on conditions of incubation and application of hormonal preparations [61,62]. It is required to search optimal methods to stimulate maturing of oocytes and ovulation process in industrial conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Normal concentrations of 17,20β-dihydroxy-4-pregnen-3-one hormone, which promote final oocyte maturation rapidly increase just prior to ovulation and spawning, and remain elevated throughout the duration of spawning activity [58][59][60]. Watering of the oocytes of loach and sturgeon fishes was stimulated in vitro by combining influence of progesterone and chorial gonadotropin on follicles [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Using a hormonal stimulation model in vitro of maturation and ovulation of sturgeon oocytes allows solving various fundamental and applied problems [3]. While the molecular mechanisms of maturation of fish oocytes were well understood [4,5], the ovulation process is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%